Competing Visions of Islam in the United States - Ahmed Hussain (International Institute of Islamic Thought, 1998)
Barring the initial works of a handful of scholars over the last 50 years, Muslim communities and their understanding of Islam in America have gone relatively unstudied in relation to other religious groups. The lacuna now, however, has been partially filled by the work of Kambiz GhaneaBassiri in a concise but complete in-way-of-issues-mentioned manner. Primarily a secondary source, it relies heavily on the initial works produced by scholars such as Yvonne Haddad, Adair T. Lummis, Earle Waugh. Aminah McCloud, and Atif Wasfi. The book is the first of a second generation of work on the subject Using a purely sociological method and lens, the book analyzes the findings of the works that came before it, coupling a case study of the views, opinions, and attitudes of different constituents of the Muslim populace of Los Angeles with the more cross-sectional approach used by the aforementioned scholars. The work raises fundamental questions regarding the validity of studying sociologically the American Muslim condition; whether a truly American Muslim condition exists; and (if it does) its characteristic features. Nevertheless, Kambiz GhaneaBassiri's work indexes, in a cartographic manner, the competing visions of Islam in the United States. Within the introduction of his work, the author outlines the purpose and methodology of his study. Departing from the writings and approach of Haddad, Lummis, Waugh, McCloud, and Wasfi, he makes his intention clear: to use surveys to examine the religious identity of Muslims in the United States by determining how they define their role as American citizens. His already enigmatic definition of a religious identity, however, being an amalgam of one's "desires," "needs," "cultural and ethnic background" and "level of religious understanding," missed certain key elements. The roles of intention and volitional acts the main components of the textual definition of Muslim identity-outlined within the Qur'an and Sunnah, more than the categories used in the study, define Muslim identity. The lack of a clear definition of Muslim identity and the inability of the study to operationalize it are the work's two main weaknesses. Nowhere in the work is it scientifically illustrated or articulated that a case study ...